Study of the temporal behavior of 4U 1728-34 as a function of its position in the color-color diagram - Di Salvo, T. (2001)
We study the timing properties of the bursting atoll source 4U 1728-34 as a function of its position in the X-ray color-color diagram. In the island part of the color-color diagram (corresponding to the hardest energy spectra), the power spectrum of 4U 1728-34 shows several features such as a band-limited noise component present up to a few tens of Hz, a low-frequency quasi-periodic oscillation (LFQPO) at frequencies between 20 and 40 Hz, a peaked noise component around 100 Hz, and one or two QPOs at kHz frequencies. In addition to these, in the lower banana (corresponding to softer energy spectra) we also find a very low frequency noise (VLFN) component below ∼1 Hz. In the upper banana (corresponding to the softest energy spectra), the power spectra are dominated by the VLFN, with a peaked noise component around 20 Hz. We find that the frequencies of the kHz QPOs are well correlated with the position in the X-ray color-color diagram. For the frequency of the LFQPO and the break frequency of the broadband noise component, the relation appears more complex. Both of these frequencies increase when the frequency of the upper kHz QPO increases from 400 to 900 Hz, but at this frequency a jump in the values of the parameters occurs. We interpret this jump in terms of the gradual appearance of a QPO at the position of the break at high inferred mass accretion rate, while the previous LFQPO disappears. Simultaneously, another kind of noise appears with a break frequency of ∼7 Hz, similar to the NBO of Z sources. The 100 Hz peaked noise does not seem to correlate with the position of the source in the color-color diagram but remains relatively constant in frequency. This component may be similar to several 100 Hz QPOs observed in black hole binaries.